Informality in Ecuador: Measuring the size of the informal sector from the perspective of inequality - Mejía Chávez, Marcelo (2023)
Informality, a common phenomenon in countries like Ecuador, affects a significant portion of the population regardless of economic size. A recent study investigated how inequality in government spending, inflation, and per capita gross domestic product (PPC) influence the persistence of informality in Ecuador. The study employed the Multiple Indicators and Multiple Causes (MIMIC) method based on a structural equation model (SEM) to analyze the impact of informality on the economy between 2001 and 2020, on a quarterly basis. Results indicated that, on average, around 32% of the national production is attributed to the informal sector, demonstrating its influence. Without effective regulations and policies, informality will increase, limiting the fight against inequality in Ecuador. Informality poses challenges to economic development and social well-being. Embracing a broad segment of the population, this sector struggles to access resources and opportunities that would enhance their quality of life. Moreover, it affects tax evasion, lack of labor protection, and unfair competition. It is vital for Ecuadorian authorities to implement appropriate policies to address informality and its impacts. This could involve incentivizing the formalization of informal activities, streamlining procedures, and improving access to financial services and training. Additionally, addressing underlying causes such as poverty, unemployment, and inadequate education is required. Confronting informality will not only strengthen the economy and living conditions but also reduce socio-economic disparities, advancing toward equitable and sustainable development